Varicella vaccination - the global experience - Peter Wutzler; Paolo Bonanni; Margaret Burgess; Anne Gershon; Marco Aurélio Sáfadi; Giacomo Casabona (Taylor & Francis Group, 2017)
Introduction: Varicella, although a frequently benign childhood disease, nevertheless represents a considerable health burden. WHO recommends including varicella vaccines in universal routine vaccination programs, and maintaining coverage >80%. Many countries have successfully introduced varicella vaccination and have benefited from lower disease burden, but many others have not adopted the vaccine. Reasons include cost commitment for a 'mild childhood disease' or concerns that vaccination will shift varicella to older age groups or increase herpes zoster incidence. Areas covered: This literature review summarizes the effectiveness and epidemiological impact of varicella immunization programs. Expert commentary: Varicella vaccines are immunogenic with acceptable safety profiles. One and two dose schedules are highly effective against varicella and large reductions in disease incidence, particularly moderate-severe disease, have been widely reported. There is currently no evidence to suggest that the introduction of varicella vaccination results in a shift of varicella disease burden to older age groups. Although epidemiological studies have shown an increased incidence of herpes zoster since the vaccines were launched, there are many other contributing factors, and indeed, this secular trend was evident before their introduction. In conclusion, varicella vaccination easily fits into existing immunization programs and significantly reduces the often underestimated burden of varicella.